Composition of Rambutan Seeds - Augustin, M. A.; Chua, B. C. (1988)
The seeds of three rambutan clones (R4, R 7 and R169) were analysed. Proximate analysis of the seeds showed that they contained 11.9-14.1% protein, 37.1-38.9% crude fat (peroleum ether extract), 2.8-6.6% crude fibre and 2.6-2.9% ash on a dry weight basis. The seeds contained 34.1-34.6% moisture. The amino acid profile of the seed protein showed that the protein was of good quality. The major fatty acids in rambutan seed fat were C16:0 (4.36-4.86%); C18:0 (5.93-7.49%); C18:1 (37.91-40.15%); C20:0 (36.14-36.77%) and C20:1 (6.92-7.27%).